REKONSTRUKSI PENGEMBANGAN KARIER JABATAN FUNGSIONAL PANITERA PENGGANTI PERADILAN DI INDONESIA - Suhariyanto, Budi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
The functional position generally managed and fostered in a nationally integrated one employment system by the fostering institution of the functional position. Unfortunately, the differentiate management and employment building occurs in the functional position of registrar, along with its judicial institution namely Supreme Court, Constitutional Court and judiciary body below Supreme Court. The different status and functional position requirement from those three judicial institutions become one of the obstacles the registrar fostering system cannot be united. For example, Constitutional Court and judiciary body under Supreme Court require civil servant as a registrar meanwhile Supreme Court Registrar is a judge. The issue of less linear and synchronization employment system led to disproportional of the fostering of registrar functional position. The career development horizontally through the application of credit points is indeed needed to construct as an expertise functional position consequences. Hence the position and career pattern does not only lead vertically to chief and deputy chief of registrar. The reconstruction of the expertise functional position of registrar should also apply the same requirement and fostering system nationally, this will lead performance and professionalism upgrading. Keywords: reconstruction, functional, registrar